The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00396-015-3744-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a pH-responsive poly(ethylene glycol)-based hydrogel: acid degradation, equilibrium swelling, and absorption kinetic characteristics

Abstract: We developed a pH-responsive, hydrogel based on poly(ethylene glycol) (PEG) covalently cross-linked with acrylic acid and N′,N′-dimethylacrylamide along with acidlabile groups. In the hydrogel, PEG plays a role as the key constituent. If its chains break, the polymer networks are destroyed. The pharmacological potential of these hydrogels were demonstrated by determining their water transport profile, modulus of elasticity, and cytotoxicity assay. The hydrogels showed a pseudo-Fickian behavior, a transport mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The HGs and nanocomposites showed values of n < 0.5, which suggests pseudo-Fickian water diffusion mechanism. Such a mechanism is found when the time needed to achieve equilibrium swelling is very long (Curcio et al, 2013;Tenório-Neto et al, 2015). Parameter k w from Weibull model is associated with the time in which HG reaches the equilibrium swelling.…”
Section: Studies On Water Transportmentioning
confidence: 99%
“…The HGs and nanocomposites showed values of n < 0.5, which suggests pseudo-Fickian water diffusion mechanism. Such a mechanism is found when the time needed to achieve equilibrium swelling is very long (Curcio et al, 2013;Tenório-Neto et al, 2015). Parameter k w from Weibull model is associated with the time in which HG reaches the equilibrium swelling.…”
Section: Studies On Water Transportmentioning
confidence: 99%
“…The experimental conditions for PEG modication as well as for hydrogel synthesis were performed according to our previous work. 12 Briey, 16 g of PEG (16 mmol) were added to 80 mL of water at 50 C while stirring. The pH of the mixture was adjusted to pH 10.5 with addition of NaOH pellets.…”
Section: Synthesis Of Macromere Based On Gma-modied Peg ( Gma Peg)mentioning
confidence: 99%
“…It has been reported that ester groups from GMA PEG structure may be cleaved, particularly in acid media, contributing to erosion mechanism. 12 On the other hand, the presence of polyacrylic acid in the hydrogel network plays a predominant role on swelling prole. The pK a of polyacrylic acid is ca.…”
Section: Swelling Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these pH responsive hydrogels have been used in medical applications, especially for drug delivery systems. The pharmacological potentials for the pH sensitive hydrogels were demonstrated by determining their water transport profile, mechanical properties, and cytotoxicity assay. Acid sensitive micro- or nanosized cross-linked hydrogel networks have also been designed and described for various biomedical applications, including living cell encapsulation, tissue engineering, and stimuli responsive controlled delivery of bioactive molecules. …”
Section: Introductionmentioning
confidence: 99%